Does productivity of Islamic banks endure progress or regress?: Empirical evidence using data envelopment analysis based Malmquist Productivity Index. Issue 1 (13th February 2017) - Kamarudin, Fakarudin; Hue, Chiun Zack; Sufian, Fadzlan; Mohamad Anwar, Nazratul Aina
Abstract : Purpose: This paper aims to explore the level of productivity of Islamic banks specifically in selected Southeast Asian Countries from the period 2006 to 2014. Besides, this study also investigates the potential determinants of bank-specific characteristics and macroeconomic conditions that may influence the productivity of banking sector. Design/methodology/approach: The present study gathers data on the 29 Islamic banks from Southeast Asian countries, namely, Brunei, Indonesia and Malaysia. The productivity level of the Islamic banks is evaluated using the data envelopment analysis-based Malmquist productivity index method. The authors then used a panel regression analysis framework based on the ordinary least square to identify potential determinants. Findings: The domestic and foreign Islamic banks have exhibited progress in total factor productivity change solely attributed to the increase in efficiency change (EFFCH) which were mainly managerial rather than scale related. Foreign-owned banks have been slightly more productive compared to their domestic-owned bank counterparts, attributed to a higher EFFCH but insignificantly different. Furthermore, capitalisation, liquidity and world financial crisis determinants have significantly influenced productivity level of Islamic banks. Originality/value: The study on the productivity of Islamic banking is still in its formative stage. To date, very limited study has been conducted to examine the productivity level in Southeast Asian, which is a strong regional hub for Islamic banking. This study intends to fill the gaps with a specific focus on the productivity level, specifically narrowing down to Southeast Asian countries in the domestic and foreign Islamic banking sector.